Portraits of people and places of developing countries : a literary analysis of the public faces of development as presented in popular literature : case study: A Small Place (1988) by Jamaica Kincaid : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Philosophy in Development Studies at Massey University - Faloon-Cavander, Jacinda (Massey University, 2006)
The literature that keeps me awake at night, containing written images that impress a certain public face of development, is the topic and exploration of this thesis. That the general public still lack in understanding regarding matters of development is key to carrying out this literature analysis. Images of the developing world are everywhere, and as such, an example of non-technical, non-industry specific creative writing is chosen for examination to highlight this point. The short, punctuating and controversial 'essay' A Small Place, by Caribbean author Jamaica Kincaid, is the case study for this thesis. The literature review is in four parts presenting the idea of public faces of development, the importance of interdisciplinary study combining literature with the humanities, an view of the underpinning contemporary themes of development - focusing on foundations of belief as opposed to physical conditions of development situations, and an introduction to Jamaica Kincaid and issues in Caribbean women's literature. Through the example of this case study, that takes its shape from close observations of the text, I conclude that popular literature has not only a literary place in ethnographic discussions, but an important historical and scientific place that helps the general reader to identify the difference between truth and fallacy represented in the various public faces of development.
Keywords: West Indies; In literature; Case studies; Social change; Developing countries; Kincaid, Jamaica; Criticism and interpretation